The Influence of Green Accounting and Corporate Social Responsibility Publications on Corporate Social Responsibility Disclosure with Financial Performance as a Moderating Variable - Intan Rahma Sari; Muliyani; Sri Putri Winingrum W.A (International Journal of Educational and Life Sciences, 2025)
The purpose of this study is to evaluate the "Effect of Green Accounting and Corporate Social Responsibility Publication on Corporate Social Responsibility Disclosure with Financial Performance as a Moderating Variable" in non-cyclical consumer and energy sector companies listed on the Indonesia Stock Exchange in 2018 to 2022. Based on the data analysis in the previous chapter, the following conclusions can be drawn, Green Accounting has no effect on Corporate Social Responsibility Disclosure, CSR Publication has no effect on Corporate Social Responsibility Disclosure, Green Accounting and CSR Publication have an effect on Corporate Social Responsibility Disclosure, Financial Performance does not moderate the effect of Green Accounting on Corporate Social Responsibility Disclosure, Financial Performance does not moderate the effect of Publication on Corporate Social Responsibility Disclosure.